This is PR the realities of public relations - Newsom, Doug.; Turk, Judy VanSlyke; Kruckeberg, Dean. (Australia Wadsworth Cengage Learning, 2013)
"Ideal for the beginning student or the experienced public relations practitioner, This is PR: The realities of public relations, Eleventh Edition, covers the world of public relations with a strong emphasis on fundamentals such as history and research, as well as emerging issues such as technology, ethics, and the international aspects. With numerous examples, strategies, tactics, and case studies, you'll have resources you can take away from the classroom."--Publisher's website.
Part 1 Public relations: Role, practice, and origins. PR roles and responsibilities PR's origins and evolution. -- Part 2 Research for PR. Research: Planning, monitoring and evaluating Stakeholders and interactions. -- Part 3 Theory, ethics and laws affecting PR practice. Theoretical underpinnings for PR PR ethics and responsibilities PR and the law. -- Part 4 PR in action. Strategic management in PR practice Communication channels and media Tactics and techniques: Details that make PR strategy work Campaigns Crisis and credibility.
Jason Baguia (recommending faculty) : Arts and Humanities Cluster
Ms. Jeneth Borlasa (Recommending faculty) : BA Mass Communication Program
Includes bibliographical references and index.
Keywords: Public relations; Communication in marketing